UPLC-Q–TOF–MS, network analysis, and molecular docking to investigate the effect and active ingredients of tea-seed oil against bacterial pathogens - Duan, Yan; Zhao, Li-Juan; Zhou, Yan-Hui; Zhou, Qi-Zhi; Fang, Ai-Qing; Huang, Yu-Ting; Ma, Yuan; Wang, Zhi; Lu, Yu-Ting; Dai, Yu-Ping; Li, Shun-Xiang; Li, Juan (Frontiers in Pharmacology, 2023)
This study, employed ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF/MS) analysis to investigate the antibacterial effect and pharmacodynamic substances of tea seed oil (TSO) combined with network analysis and molecular docking. Specifically, the major chemical components in the methanol-extracted fractions of TSO were subjected to UPLC-Q-TOF-MS. The methanol-extracted fractions contained a total of 47 chemical components, predominantly consisting of unsaturated fatty acids and phenolic compounds. The network pharmacology analysis demonstrated that various components, including gallocatechin, gallic acid, epigallocatechin, theophylline, chlorogenic acid, puerarin, and phlorizin, possess the ability to interact with critical core targets such as serine/threonine protein kinase 1 (AKT1), epidermal growth factor receptor (EGFR), a monoclonal antibody to mitogen-activated protein kinase 14 (MAPK14), HSP90AA1, and estrogen receptor 1 (ESR1). Furthermore, these components can modulate the phosphatidylinositol-3-kinase protein kinase B (PI3K-AKT), estrogen, MAPK and interleukin 17 (IL-17) signaling pathways, hereby exerting antibacterial effects. The results of the molecular docking analysis demonstrated the strong binding properties of the core components and targets. To assess the inhibitory effects, the minimum inhibitory concentration and diameter of the bacteriostatic circle were measured for the potential active ingredients and their equal ratios of combinatorial components (ERCC) against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans. Moreover, the quantification of the active constituents within TSO was accomplished through the utilization of high-performance liquid chromatography (HPLC). The primary objective of this investigation is to establish a scholarly foundation for the advancement and utiliczation of versatile TSO.